Pengaruh Kualitas Produk, Kualitas Layanan, dan Nilai NasabahTerhadap Kepuasan dan Loyalitas Nasabah Bank “XY”Cabang Kapuas - Yano Sudarto; Dwi Wahyu Artiningsih; M. Noor Rasyidi (JURNAL BISNIS DAN PEMBANGUNAN, 2016)
This study aims to determine the effect of Quality of Service, Product Quality, Value Customer Satisfaction and Customer Loyalty Bank "XY" Branch Kapuas. Using a quantitative approach to the design of causality between variables and Ex Post Facto through hypothesis testing.Samples collected in this study as many as 42 samples where all populations are sampled. Sampling in this study using the technique of accidental sampling with Likert scale. Data analysis technique that used the model approach PLS (Partial Least Square) using t-test through smartPLS test equipment.Results of the research hypothesis testing via t-test showed that the Quality of Service, Quality Products, and Value significant effect on the Customer Satisfaction and Customer Loyalty Bank "XY" Branch Kapuas. However, hypothesis testing via t-test on variables Service Quality is not significant effect on the Bank Customer Loyalty "XY" Branch Kapuas with a value of 0,106303%. Keywords: quality of service, product quality, customer value, customer satisfaction and customer loyalty